2016
DOI: 10.1007/s00467-016-3474-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of renal angiomyolipoma in tuberous sclerosis complex (TSC) patients

Abstract: In adult tuberous sclerosis complex (TSC) patients, renal complications are the leading cause of death. Beginning in childhood, up to 80 % of patients develop renal angiomyolipoma characterized by a size-dependent risk of life-threatening bleeding. After discovery of the two causative genes, TSC1 and TSC2, and the role of mammalian target of rapamycin (mTOR) regulation in the pathogenesis of TSC, an increasing number of clinical studies evaluating mTOR inhibition in TSC patients have shown impressive results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 64 publications
0
18
0
2
Order By: Relevance
“…Angiomyolipomata are the most common renal manifestations in patients with tuberous sclerosis complex (TSC) developing during later childhood and adolescence. [ 1 , 2 ] Renal angiomyolipomata are benign tumors composed of blood vessels, smooth muscle, and adipose tissue. [ 3 ] They belong to a family of neoplasms called perivascular epithelioid cell tumors (PEComas) which include pulmonary lymphangioleiomyomatosis (LAM).…”
Section: Introductionmentioning
confidence: 99%
“…Angiomyolipomata are the most common renal manifestations in patients with tuberous sclerosis complex (TSC) developing during later childhood and adolescence. [ 1 , 2 ] Renal angiomyolipomata are benign tumors composed of blood vessels, smooth muscle, and adipose tissue. [ 3 ] They belong to a family of neoplasms called perivascular epithelioid cell tumors (PEComas) which include pulmonary lymphangioleiomyomatosis (LAM).…”
Section: Introductionmentioning
confidence: 99%
“…The size of aneurysm could be reduced due to shrinkage of vasculature by mTOR inhibitor therapy, and it might explain why the marked shrinkage of TSC-AML is associated with a very low incidence of hemorrhage 10. The only mTOR inhibitor approved for the treatment of TSC- AML is everolimus, which is indicated in the treatment of patients with AML who are at risk of complications but do not need immediate surgery 11. The International TSC Consensus Conference Guidelines (2012) recommend initiating mTOR inhibitor therapy in patients with TSC who have at least one growing, asymptomatic AML >3 cm in diameter 12.…”
Section: Discussionmentioning
confidence: 99%
“…Brakemeier et al published a review of mammalian target of rapamycin inhibitor treatment for TSC patients and emphasized that TSC patients, especially children, have to be closely monitored during the administration of everolimus for the following reasons: (i) most patients with TSC require long-term treatment; (ii) fat-poor renal tumors with a high degree of vascularization, which are difficult to distinguish from renal malignancies, can be presumed to be AML if they show an early response to everolimus treatment; and (iii) the optimal dosage of everolimus for AML in TSC remains unclear. 3 The article by Hatano et al showed for the first time the effectiveness of intermittent everolimus treatment for renal AML associated with TSC. 4 After the administration of everolimus, all of the AMLs shrank, and the AMLs in eight out of 26 patients remained smaller after the withdrawal of everolimus.…”
Section: Editorial Commentmentioning
confidence: 99%